2016
DOI: 10.1007/s00464-016-5149-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with difficult gastric endoscopic submucosal dissection: predicting difficult ESD

Abstract: Difficult ESD procedures are a function of the lesion size and location, submucosal fibrosis, and submucosal invasive cancer. When a difficult ESD procedure is expected, appropriate preparations should be considered, including consultation with more experienced endoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 21 publications
3
57
0
Order By: Relevance
“…In contrast, the J‐WEB/EGC study is very important because this study is the only study to demonstrate the factors associated with a long ER procedure time in a prospective, large consecutive series of patients undergoing ER not only for EGC in the naive stomach but also for EGC in the remnant stomach/gastric tube and local recurrent EGC lesions, in accordance with the actual clinical settings. Similar to previous retrospective studies, our multivariate analysis showed that a larger tumor size (>20 mm), tumor location (upper‐third and middle‐third), and UL findings were significantly associated with a long ESD procedure time . Additionally, this study demonstrated that a local recurrent lesion, gastric tube, male gender, and tumor depth (SM) were also significant predictors of a long ESD procedure time.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, the J‐WEB/EGC study is very important because this study is the only study to demonstrate the factors associated with a long ER procedure time in a prospective, large consecutive series of patients undergoing ER not only for EGC in the naive stomach but also for EGC in the remnant stomach/gastric tube and local recurrent EGC lesions, in accordance with the actual clinical settings. Similar to previous retrospective studies, our multivariate analysis showed that a larger tumor size (>20 mm), tumor location (upper‐third and middle‐third), and UL findings were significantly associated with a long ESD procedure time . Additionally, this study demonstrated that a local recurrent lesion, gastric tube, male gender, and tumor depth (SM) were also significant predictors of a long ESD procedure time.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have described factors associated with a long ER procedure time based on retrospective analyses . In contrast, the J‐WEB/EGC study is very important because this study is the only study to demonstrate the factors associated with a long ER procedure time in a prospective, large consecutive series of patients undergoing ER not only for EGC in the naive stomach but also for EGC in the remnant stomach/gastric tube and local recurrent EGC lesions, in accordance with the actual clinical settings.…”
Section: Discussionmentioning
confidence: 83%
“…Among a total of 18 articles identified, the perforation rate was 3.02% (512/16 941) and 98.8% of patients (506/512) recovered without surgical intervention . Risk factors for intraoperative perforation during gastric ESD are listed in Table .…”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
“…For location, upper third, middle third,greater curvature and remnant stomach, were reported to be high‐risk areas for intraoperative perforation. Other risk factors included tumor size, invasion depth,submucosal fibrosis, elevated macroscopic type and old age . Long procedure time and piecemeal resection were also reported to be associated with the incidence of perforation, those might be due to not only tumor‐related factor but also the endoscopist‐related factor.…”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
“…Presence of submucosal fibrosis is associated with increased procedure time and risk of adverse events in both endoscopic submucosal dissection (ESD) and POEM . Here, we used the same classification of submucosal fibrosis described by Jeong et al .…”
Section: Methodsmentioning
confidence: 99%